Spatial characteristics of gully erosion and slope in Sinjar District: Geomorphological study - Mohammed, Jamila (Al-Adab Journal, 2025)
The research aims to conduct a geomorphological analysis of the spatial relationships between gully erosion and slopes in Sinjar District, relying on the correspondence between gully erosion maps and degrees of slope and the correspondence between gully erosion maps and the valley network, by identifying the natural factors and their geomorphological role in the occurrence of gully erosion in Sinjar District, the research was able to determine the rate of gully erosion per (km2) according to the Bergsma system for degrees of erosion. It has been found that Sinjar District suffers from water erosion in its various scopes within all slope levels in general and suffers in particular from the dominance of light and medium erosion zones in the lower and middle slopes of the Sinjar Mountain range, in addition to its dominance within the upper parts of the slopes of the Sinjar Mountains.